Vino kot ponudba v oskrbovalnih verigah in turistično doživetje na deželi - Papler, Drago (Trajnost, 2025)
Slovenia has 505,255 hectares of agricultural land with 67,747 agricultural holdings, of which 14,096 hectares are vineyards with 17,442 holdings. Wine quality and excellent marketing have become the most important elements in viticulture and winemaking. Goriška Brda has 1 800 hectares of vineyards. The most famous wines are the indigenous Rebula, Tokaj, Pinot, Pinot Gris, Chardonnay, Savignon, Merlot and Cabernet. Goriška Brda has a sub-Mediterranean climate, with twice the annual rainfall of the Mediterranean climate. The clay subsoil has given rise to deep loamy to clayey loam soils that are well permeable to water and full of minerals, which offer good conditions for the growth of vines and thus a higher mineral note in the wine. The case study shows the Ronk estate, which has three brands, Frajer, Ronk and the new Selectus. Launching the new brand was a challenge of marketing know- -how in the supply chain, hard work and application of experience. The importance of the new brand is differentiation, quality guarantee, advertising, competition and origin labelling, and a distinctive image of the tourist experience in the country, recognised by loyal customers.
Keywords: blagovna znamka; statistična analiza; trženjski splet; turizem; vino